Analisis Pengalaman Mahasiswa terhadap Efektivitas Aplikasi Gojek dalam Layanan Transportasi Online - Meiranda Siregar; Muhammad Irwan Padli Nasution (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
Online transportation services have become an important part of student life because they provide ease of access, time efficiency, and mobility flexibility. The Gojek application is one of the most frequently used services by students in Medan City to support academic and non-academic activities. This study aims to analyze students' experience in using the Gojek application and its effect on the effectiveness of the application in online transportation services. The research method used was a quantitative approach with survey techniques through a Likert scale questionnaire (1–5) to 50 students who were active users of Gojek. Data were analyzed using descriptive statistics and simple linear regression. The results showed that user experience (UX) was in the category of quite good with an average value of 3.58, while the effectiveness of the application was in the category of quite good with an average of 3.47. The reliability test showed Cronbach's Alpha values of 0.935 (UX) and 0.951 (Effectiveness), which means the instrument is very reliable. The results of the regression analysis showed that user experience had a positive and significant effect on the effectiveness of the application (β = 0.961; R² = 0.881; p < 0.001). Thus, the better the student experience in using the Gojek application, the higher the effectiveness felt in online transportation services. These findings confirm that improving the quality of user experience is a key factor to maintain and increase the effectiveness of online transportation applications among students.